INDEKS BAHAYA EROSI DI SUB DAS PASUI HULU DAS SADDANG: Erosion Hazard Index in Upstream Sub Watershed Pasui of Saddang Watershed - Lia Asmira; Syamsul Arifin Lias; Sartika Laban (Jurnal Ecosolum, 2022)
Sub watershed Pasui is an upstream area of Saddang watershed with mountain topography dominated by agricultural cultivation activities of coffee, cocoa, cloves and onions without conservation methods. Agricultural cultivation activities that do not apply conservation methods on steep slopes are expected to increase the rate of erosion in this region. This study is aim to determine the magnitude of potential erosion and erosion hazard index in Sub watershed Pasui upstream Saddang watershed. The method of study is conducted survey and soil sampling in Sub watershed Pasui, Baraka subdistrict and Buntu Batu, Enrekang regency. The study took place from February to August 2021. Erosion restoration uses the USLE method, while the restoration of erosion hazard index refers to The Minister of Forestry Regulation No. 60 of 2014. Paddy field cover, mixed dry land agriculture and forest are classified as low erosion hazard index class with potential erosion value <15 ton/ha/year. Meanwhile, dry land and savanna agriculture belong to a very high erosion hazard index class with a potential erosion value. The weighted average potential erosion value is 189,46 tons/ha/year, while the weighted average erosion hazard index in the Sub watershed Pasui upstream Saddang watershed is 8,83 and belongs to the highest erosion hazard class.